Efeitos da opacidade no estudo da turbulência interestelar - Correia, Caio Fábio Teixeira (2015)
In this work we study the goodness of estimating sonic Mach number (MS) from linewidths of 13CO in molecular clouds of the interstellar medium, taking effects of opacity into account. To do so, we analyze magnetohydrodynamic simulations including post processed radiative transfer to simulate radio observations of real clouds. We have found a very good agreement for the measured MS and the real one, available from simulations. However, we find that the opacity broadening of CO linewidths in optically thick media causes an overestimation ofMS by a factor of 1:16 1:3. Also we find that this overestimation depends on the molecular cloud magnetic field. Super-Alfvénic turbulence (weak magnetic fields) will present larger linewidth broadening in comparison to sub-Alfvénic simulations (strong magnetic fields) in all range of optical depths investigated. This restuls have implications to the observationally derived relationship between the column density standard deviation ( N=hNi) and the sonic Mach numberMSof the cloud. Adding to that, we investigate the capacity of the Principal Component Analysis (PCA) technique in detecting changes of the velocity power spectrum in high opacity regimes. For this, we include synthetic observations of CO in fractional Brownian Motion (fBm) and MHD simulations. Our results indicate that PCA can detect changes of the velocity power spectrum even in high opacity regimes, and that this is caused its sensibility to phase information as well as spectral information of the observations, in contrast with other techniques based solely on spectral information, which saturates to a spectral index of B ~ - 3, in optically thick environments.